Using Normalized Difference Vegetation Index (Ndvi) To Assessment The Changes Of Vegetations Cover In Surrounding Area Of Himreen Lake - Ahmed, Mousa; Ahmad, Walid (Iraqi Journal of Science, 2024)
The study area lies in the eastern part of Iraq, within Diyala and small parts of Salah Al-Din and Sulamanyah Governorates. The eastern boundary of the map represents Iraqi-Iranian International borders; it covers about 7001 Km2.The present study depends on two scenes of Thematic Mapper (TM5) data of Landsat and one scene of Multi-Spectral Scanner (MSS) data of Landsat, these data are subset and corrected within the ERDAS 9.2 software using UTM N38 projection. Normalized Difference Vegetation Index (NDVI) was adopted as practical tool for monitoring the surrounding area of Himreen Lake. The obtained result shows the distributions of NDVI for period 1976-1992 were positive pattern of (High vegetation density and Moderate vegetation density) and negative pattern of (Low vegetation density).The distributions of NDVI for period 1992-2010 was negative pattern of (High vegetation density and Low vegetation density) and positive pattern of (Moderate vegetation density).